Effects of a forest pathogen on habitat selection and quality for the endangered golden‐cheeked warbler - Laura R. Stewart; Michael L. Morrison; Mark R. Hutchinson; David N. Appel; R. Neal Wilkins (Wildlife Society Bulletin)
ABSTRACT Oak wilt is a fatal forest disease caused by the fungus Ceratocystis fagacearum. Loss or degradation of habitat caused by oak wilt may negatively affect forest songbirds, including the federally endangered golden‐cheeked warbler (Setophaga chrysoparia), a species that breeds exclusively in the Ashe juniper–oak woodlands (Juniperus ashei–Quercus spp.) of central Texas, USA. During 2010 and 2011, we investigated the influence of oak wilt on golden‐cheeked warbler habitat selection and quality at 25 study sites that each contained forest affected by oak wilt and unaffected forest. We assessed habitat selection in terms of use versus availability at 2 scales: within the patch and within the territory. We also assessed post‐breeding use of affected forest by comparing detection densities in affected and unaffected forest. To assess the influence of oak wilt on habitat quality, we compared the reproductive outcome of territories in unaffected and affected areas. We assessed within‐patch habitat selection for 67 territories and found that golden‐cheeked warblers used affected forest significantly less than its availability. We found use of affected forest to be variable within the 14 territories that contained affected forest in >10% of their area. Post‐breeding use of affected forest was also variable. Pairing success was 27% lower for males whose territories contained >10% affected forest but fledging success was not affected. Our results suggest that the presence of oak wilt negatively influences habitat selection and quality for golden‐cheeked warblers, likely due to reduced canopy cover in susceptible oak species. © 2013 The Wildlife Society.